2018
DOI: 10.3390/v10050227
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Modulation of CD8+ T Cell Function in Lentivirus Infections: A Review

Abstract: CD8+ T cells are critical for controlling viremia during human immunodeficiency virus (HIV) infection. These cells produce cytolytic factors and antiviral cytokines that eliminate virally- infected cells. During the chronic phase of HIV infection, CD8+ T cells progressively lose their proliferative capacity and antiviral functions. These dysfunctional cells are unable to clear the productively infected and reactivated cells, representing a roadblock in HIV cure. Therefore, mechanisms to understand CD8+ T cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 169 publications
0
2
0
Order By: Relevance
“…[10] Epigenetic modulation reduces the FOXP3 binding to interleukin (IL)-2, tumor necrosis factor (TNF)-α, and interferon (IFN)-γ promoters in lentivirus-specific CD8 + T cells. [11] At the same time, with epigenetic modulation, reduced expression of co-stimulatory molecules like CD40, CD80, CD86 and secretion of pro-inflammatory cytokines including TNF-α, IL-1β, IL-6 and IL-12 inhibits the activation of Th1 and Th17 responses and granzyme B producing CD8 + T cells. [12,13] However, recently epigenomic and transcriptomic regulome revealed that HBVspecific CD8+ T cells which are not terminally exhausted showed long-term memory and polyfunctionality in chronically HBV-infected HCC patients.…”
Section: Introductionmentioning
confidence: 99%
“…[10] Epigenetic modulation reduces the FOXP3 binding to interleukin (IL)-2, tumor necrosis factor (TNF)-α, and interferon (IFN)-γ promoters in lentivirus-specific CD8 + T cells. [11] At the same time, with epigenetic modulation, reduced expression of co-stimulatory molecules like CD40, CD80, CD86 and secretion of pro-inflammatory cytokines including TNF-α, IL-1β, IL-6 and IL-12 inhibits the activation of Th1 and Th17 responses and granzyme B producing CD8 + T cells. [12,13] However, recently epigenomic and transcriptomic regulome revealed that HBVspecific CD8+ T cells which are not terminally exhausted showed long-term memory and polyfunctionality in chronically HBV-infected HCC patients.…”
Section: Introductionmentioning
confidence: 99%
“…They are highly infectious and extremely harmful, particularly lentiviruses such as human immunodeficiency virus, and the medical community has not yet found an efficient and reasonable treatment strategy. 13 Recently, researchers have found that lentiviral nucleocapsids play a crucial role in the lentiviral replication cycle and are considered ideal targets for antiviral therapy. 14 Detecting the temperature changes that accompany nucleocapsid binding and exploring the effects of temperature changes on the activity of proteases and reverse transcriptases, helps to deepen the understanding of lentiviral replication and develop more efficient and rational lentiviral treatment strategies.…”
Section: Introductionmentioning
confidence: 99%